Self-reported training stress and perceived effort among Norwegian upper secondary school students - Shaher A. I. Shalfawi; Henrik Egeland (Journal of Applied Sports Sciences, 2025)
Background: This study investigated training distress and perceived exertion among Norwegian upper secondary school students in sports and physical education programs. Specifi cally, it sought to explore whether diff erent Athlete Self Report Measures (ASRM) provided similar indications of training distress. Methods: Ninety-four upper secondary school students who enrolled in a sports and physical education program were followed over time using a longitudinal research design. For 12 weeks, participants reported the duration and Rate of Perceived Exertion (RPE) for each training session. Concurrently, the students completed the Multi-Component Distress Scale (MTDS) and the Oslo Sports Trauma Research Centre (OSTRC-H2) injury/illness questionnaire once a week. Results: A marked correlation was observed between the MTDS and RPE scores among Grade 3 students (graduate students), with girls contributing the most to the statistically signifi cant correlations. The most considerable diff erences in training distress between boys and girls were observed among Grade 3 students, recreational athletes, and football players. Additionally, the data suggested that girls experienced higher injury and illness rates than boys. Conclusions: The study found that the MTDS was more eff ective than RPE in assessing weekly training distress among Grade 3 students. Moreover, the results showed that an increase in physical distress, as measured by the MTDS, was associated with a higher likelihood of injury and/or illness among Grade 3 girls. In contrast, psychological distress was linked to a greater risk of injury and/or illness among Grade 3 boys. Although both ASRM instruments used in this study have been validated, we recommend that the MTDS be used as a supplementary tool rather than the primary instrument for assessing training distress.